Changes in the community structure of the symbiotic microbes of wild amphibians from the eastern edge of the Tibetan Plateau - Liang Liang Xu; Hua Chen; Mengjie Zhang; Wei Zhu; Qing Chang; Guoqing Lu; Youhua Chen; Jianping Jiang; Lifeng Zhu (MicrobiologyOpen, 2020)
Abstract Environment has a potential effect on the animal symbiotic microbiome. Here, to study the potential relationship of the symbiotic microbiomes of wild amphibians with altitude, we collected the gut and skin samples from frogs (nine species) and the environmental samples (water and soil samples) from the Leshan Mountains (altitude: 360–410 m) and Gongga Mountains (altitude: 3340–3989 m) on the eastern edge of the Tibetan Plateau. Bufo gargarizans (Bg) samples were collected from both the Leshan and Gongga mountain regions (Bg was the only species sampled on both mountains). The DNA extracted from each sample was performed high‐throughput sequencing (MiSeq) of bacterial 16S rRNA gene amplicons. High relative abundance of Caulobacteraceae and Sphingomonadaceae was found in skin samples from both Bg and the other high‐altitude amphibians (nine species combined). High relative abundance of Coxiellaceae and Mycoplasmataceae was found in gut samples from both Bg and the other high‐altitude amphibians. Furthermore, the alpha and beta diversities of skin and gut samples from Bg and the other amphibian species (nine species combined) were similar. In terms of the symbiotic microbial community, the low‐altitude samples were less diverse and more similar to each other than the high‐altitude samples were. We speculated that extreme high‐altitude environments and host phylogeny may affect the amphibian microbiome. Despite the distinct microbial community differences between the skin and gut microbiomes, some functions were similar in the Bg and combined high‐altitude samples. The Bg and high‐altitude skin samples had higher oxidative stress tolerance and biofilm formation than the low‐altitude skin samples. However, the opposite results were observed for the Bg and high‐altitude gut samples. Further study is required to determine whether these characteristics favor high‐altitude amphibian adaptation to extreme environments.